Предмет: Математика,
автор: musayevyusif09032007
пж помогите с решением
Приложения:
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
(5x^2+9)/6-(4x^2-9)/3=3x. Приведем к общему знаменателю 6.
5x^2+9-2*(4x^2-9)=6*3x
5x^2+9-8x^2+18-18x=0
-3x^2-18x+27=0. Разделим на (-3)
x^2+6x-9=0. D=36-4*(-9)=72
x1=(-6+6√2)/2=-3+3√2. x2=(-6-6√2)/2=-3-3√3
(x1+x2)/2=(-3+3√2-3-3√2)/2=-6/2=-3 -это ответ Е).
Похожие вопросы
Предмет: Окружающий мир,
автор: 12345966
Предмет: Русский язык,
автор: сергей514
Предмет: Русский язык,
автор: мерей29
Предмет: Музыка,
автор: БЕРЕНА
Предмет: ОБЖ,
автор: shavalieva200458